Recent Advances on the Applications of Luminescent Pb2+-Containing Metal–Organic Frameworks in White-Light Emission and Sensing - Wang, Li-Xin; Xiang, Jing; Li, Chuan-Hua; Leung, Chi-Fai; Xiang, Jing (Frontiers in Chemistry, 2021)
Luminescent Pb2+-based metal-organic frameworks (MOFs) belong to a new class of multifunctional molecular materials with interesting luminescence properties and potential applications within a single crystalline phase. In this mini review we present the recent advances that have been achieved in their applications as single-phase white-light emitting materials and chemosensors in the last decade. We focus on the trends in the modification of their structures and luminescence by various bridging ligands, and subsequently their multi-functional applications, which may affect the future development of the field.